The Gruffalo's child - Donaldson, Julia; Scheffler, Axel (New York : Dial Books for Young Readers, 2005)
The Gruffalo's Child goes out to find the Big Bad Mouse she has heard so much about.
Horn Book.
Publisher's Weekly.
2.4
K-3
Keywords: Animals -- Juvenile fiction; Curiosity -- Juvenile fiction; Mice -- Juvenile fiction; Animals -- Fiction; Curiosity -- Fiction; Mice -- Fiction; Stories in rhyme; Animals -- Fiction; Curiosity -- Fiction; Mice -- Fiction; Stories in rhyme